ระดับเหล็กสะสม (serum ferritin) ในผู้บริจาคโลหิตที่มีภาวะเลือดลอย จากการตรวจโดยวิธีคอปเปอร์ซัลเฟต: Serum Ferritin Levels among Blood Donors Who Failed the Initial Screen for Anemia by Copper Sulfate Method - Maneemaroj, Ratchaneewan; Klunklin, Kanokwan; Tunkvorasitichai, Surapon; Meemak, Suvadee (Asian Health, Science and Technology Reports, 2011)
การศึกษานี้เพื่อตรวจหาระดับเหล็กสะสม (serum ferritin) และฮีโมโกลบิน (Hb) ในผู้บริจาคโลหิตที่มีภาวะเลือดลอย โดยใช้เลือดของผู้บริจาคโลหิตที่มีภาวะเลือดลอยจากการตรวจด้วยวิธีcopper sulfate จำนวน 190 ราย จากการศึกษาในกลุ่มผู้บริจาคโลหิตประจำ (regular donor) และผู้บริจาคโลหิตครั้งแรกหรือครั้งที่สอง (non-regular donor) พบจำนวนผู้บริจาคโลหิตที่มีภาวะขาดธาตุเหล็ก (serum ferritin <15 ng /ml) 28.9% และ 3.9% ตามลำดับ พบว่ามีฮีโมโกลบิน (Hb) ต่ำกว่าปกติ (<12 g/dl ในเพศหญิง และ <13 g/dl ในเพศชาย) 42.1% และ 43.5 % ตามลำดับ และพบภาวะโลหิตจางจากการขาดธาตุเหล็ก (serum ferritin <15 ng /ml ร่วมกับฮีโมโกลบิน (Hb) ต่ำกว่าปกติ) 17.5% และ 1.3% ตามลำดับและส่วนใหญ่เป็นเพศหญิง นอกจากนี้ยังพบความสัมพันธ์ของเหล็กสะสม (serum ferritin) กับฮีโมโกลบิน (Hb) ความถี่ของการบริจาคโลหิต และจำนวนครั้งในการบริจาคโลหิตที่p<0.01 และยังพบค่ากลางของเหล็กสะสม (serum ferritin) ในผู้บริจาคโลหิตประจำและผู้บริจาคโลหิตครั้งแรกหรือครั้งที่สองเพศหญิงมีความแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ p<0.05 สรุปว่าการบริจาคโลหิตเป็นประจำโดยไม่ได้รับธาตุเหล็กทดแทนอย่างเพียงพออาจก่อให้เกิดภาวะโลหิตจางจากการขาดธาตุเหล็กหรือภาวะขาดธาตุเหล็กแตยั่งไมแ่ สดง ภาวะโลหติ จางไดใ้ นผบู้ รจิ าคบางกลมุ่ โดยเฉพาะผบู้ รจิ าคเพศหญิง ดังนนั้ ควรพจิ ารณาตรวจระดับเหล็กสะสม (serum ferritin) ให้ผู้บริจาคโลหิตประจำเพศหญิง และควรพิจารณาการตรวจคัดกรองภาวะซีดของผู้บริจาคโลหิตโดยวัดค่าฮีโมโกลบิน (Hb) โดยตรงแทนการใช้สารละลาย copper sulfate This study aims to determine serum ferritin and hemoglobin levels in 190 voluntary blood donors who failed the initial screen for anemia by copper sulfate method. The results found that regular donors with deficient iron storage (serum ferritin <15 ng /ml) was 28.9% compared to 3.9% of the first or second time blood donors. Low level of hemoglobin (hemoglobin <12 g/dl in female and <13 g/dl in male) was also found in 42.1% and 43.5% of regular and the first or second time blood donors respectively. Regular donors with iron deficiency anemia (serum ferritin <15 ng /ml and hemoglobin <12 g/dl in female and <13 g/dl in male) have higher number than the first or second time blood donors (17.5% and 1.3% respectively) and almost all of them were female. We found significant correlations between serum ferritin and hemoglobin level, the frequencies and the number of donations at p<0.01 and also found the significant differences median of serum ferritin level between regular and the first or second time female donors at p<0.05. We conclude that there are a large proportion of female regular blood donors with iron deficiency anemia or iron deficiency without anemia. Serum ferritin determination may be needed in female regular donors and quantitative hemoglobin assessment should be performed to screen for appropriate blood donors.